STUDI AWAL PENGOLAHAN LIMBAH CAIR TAPIOKA DENGAN PHOTOKATALITIK MENGGUNAKAN ENERGI SURYA - V. Paramita; M. E. Yulianto; I. Hartati (JURNAL ILMIAH MOMENTUM, 2006)
The development of tapioca industry has an impact on the increasing of the organic wastewater quantity. The  tapioca wastewater has to be pretreated before it thrown away to the environment. The expensive wastewater treatment process  can be done only by an establish company, thus small scale industries can not  yet adopt the treatment process because of    economical reason. If small scale industries are compelled to adopt it, then it would be a burden for them. In order to solve that problem, it is necessary to develop a new wastewater treatment process that  is  achievable. One of the alternatif process is photocatalytic treatment using solar energy. The objective of this research was to find out the COD descent of the tapioca wastewater,  whereas COD is one of the parameter that can indicated the pollution level. The type of the research was a simple experimental design which was “ only control group design” . The experimental variables were time and  TiO2 as the free variable, COD consentration as the fixed variable, COD initial concentration and the volume of TiO  solution as the controlled variable. The wastewater  that  was  used in the research was a synthetic tapioca wastewater. The result of the research was a primer data, which descriptively, the data showed that  the descent of COD concentration was varried between 84,1 % to 95,6 %. The highest descent was obtained from the experiment that’s carried for 180 minutes and the  TiO2 concentration was 0,085%, while the lowest descent was obtained from the experiment that’s carried for 20 minutes and the  TiO2 concentration was 0,028%. Analytically, the data were proved normally distributed. Two ways annova test gave a very significant value of p and α, which are 0,000 and 0,05, respectively. The Dunken Test was used to find the most effective condition, and we found that 180 minutes  time of reacion and TiO2 concentration of  0,085% were the most effective condition. Photocatalytic treatment of tapioca wastewater using solar energy could descent its COD concentration up to 95,6%. Key Words : Tapioca wastewater, COD, photocatalytic, sun energy, environmental friendly.